A novel CTLA-4 deletion variant in a child with refractory autoimmune hemolytic anemia: molecular and functional characterization - Chen, Feng; Lei, Siyu; Yuan, Caihui; Xu, Zhongjin; Wan, Qian; Wu, Chongjun; Xiong, Ting (Frontiers in Immunology, 2025)
ObjectiveAs a critical immune checkpoint, cytotoxic T-lymphocyte-associated protein 4(CTLA-4)deficiency is a well-established cause of inborn errors of immunity. This study characterizes a novel CTLA-4 deletion variant identified in a pediatric case of refractory autoimmune hemolytic anemia (AIHA), with the aim of delineating the clinical profile and elucidating the underlying pathogenic mechanism.MethodsTrio-based whole-exome sequencing (WES) was performed on peripheral blood samples from a 6-year-old female with refractory AIHA and her parents. Candidate variants were validated by Sanger sequencing. Structural modeling of mutant CTLA-4 was conducted, followed by in vitro functional assays in 293T cells to assess mRNA transcription (qPCR) and protein expression (Western blot).ResultsA CTLA-4 (c.362_391del) variant was identified within the immunoglobulin V-set domain of the CTLA-4 protein. In vitro experiments demonstrated significant reductions in both mRNA and protein expression levels caused by this variant.ConclusionThe CTLA-4 (c.362_391del) variant may contribute to refractory AIHA in children. This case highlights the potential necessity of including CTLA-4 variants in the differential diagnosis of pediatric AIHA, particularly when conventional therapies prove ineffective, and warrants further validation in larger cohorts.